Chipless RFID: Design Procedure and Detection Techniques - Rezaiesarlak, Reza (Springer, 2015)
This book examines the design of chipless RFID systems. The authors begin with the philosophy of RFID and its effect on commercial applications. Then, they discuss the chipless RFID systems and the application of chipless RFID systems, the advantages it provides compared to conventional barcode ID and chipped RFID tags. The text then covers chipless RFID components in block diagram representation and introduce FCC requirements which should be considered in the design procedure of each component. The third chapter is dedicated to the complex natural resonance-based design of chipless RFID tags. The next chapter concerns about the detection techniques introduced for the identification of chipless RFID tags. The fifth chapter is dedicated to the localization and anti-collision techniques in chipless RFID systems. Final chapter is chipless RFID tags as sensors. It provides some applications where the tag can be used as both ID and sensor. The tag specifications and detection issues are addressed in this section.